Adhesive film

Through the surface protective film adhesive layer of acrylate polymer with a crosslinking agent with a specific structure combined with an antistatic agent, the problem of difficulty in controlling the adhesive strength and preventing glue residue in low-speed and high-speed areas in the prior art is solved, and the multiple performance requirements of optical components in the manufacturing process of liquid crystal displays are realized.

JP2025016732AActive Publication Date: 2025-02-04ZACROS CORP
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2024194337
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-04
Estimated Expiration
2033-07-23

AI Technical Summary

Technical Problem

The prior art is difficult to balance the adhesive strength in low-speed and high-speed areas to prevent glue residues, and has excellent antistatic properties and reprocessing properties, making it difficult to meet the multiple needs of the surface protective film of optical components during the manufacturing process of liquid crystal displays.

Method used

Acrylate polymers and crosslinking agents containing specific structures are used to combine antistatic agents with specific structures to form a crosslinking structure with specific molecular weight and melting point, and are used to prepare an adhesive layer for the surface protective film.

Benefits of technology

It achieves balanced bonding strength in low-speed and high-speed areas, prevents glue residue, and has excellent anti-static and reprocessing properties, which is suitable for surface protection of optical components during the manufacturing process of liquid crystal displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016732000001
    Figure 2025016732000001
  • Figure 2025016732000002
    Figure 2025016732000002
  • Figure 2025016732000003
    Figure 2025016732000003
Patent Text Reader

Abstract

To provide an adhesive film that has excellent antistatic performance, a good balance of adhesive strength at peeling speeds in a low speed region as well as a high speed region, and further has excellent durability performance and rework performance.SOLUTION: An adhesive film comprises an adhesive layer(s) formed on one surface or both surfaces of a resin film, the adhesive layer being formed by crosslinking an adhesive composition comprising: an acrylic polymer comprising an alkyl (meth)acrylate having a C4-10 alkyl group as a main component, where the acrylic polymer comprises, relative to 100 pts.wt. thereof, 85-98.5 pts.wt. of the main component alkyl (meth)acrylate, (500 / 101)-15 pts.wt. of a copolymerizable monomer containing a hydroxyl group, 0.1-(100 / 99.5) pts.wt. of a copolymerizable monomer containing a carboxylic group, and 0.1-5 pts.wt. of a crosslinking agent, where the acrylic polymer has an acid value of 0.01-8.0; and an antistatic agent comprising an ionic compound with a melting point of 30-50°C. The adhesive film has adhesive force of 0.05-0.1 N / 25 mm at a peeling speed of 0.3 m / min and adhesive force of 1.0 N / 25 mm or less at a peeling speed of 30 m / min.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive composition having antistatic properties, and to a pressure-sensitive adhesive film and a surface protection film in which a pressure-sensitive adhesive layer having antistatic properties is formed on at least one surface of a resin film using the pressure-sensitive adhesive composition. The present invention also relates to a surface protection film used in the manufacturing process of a liquid crystal display. More specifically, the present invention relates to a pressure-sensitive adhesive composition for a surface protection film used to protect the surfaces of optical members such as a polarizing plate, a retardation plate, and an anti-reflection film by being attached to the surfaces of optical members such as a polarizing plate, a retardation plate, and an anti-reflection film that constitute a liquid crystal display, and a surface protection film using the same. [Background technology]

[0002] Conventionally, in the manufacturing process of optical members such as polarizing plates, retardation plates, and anti-reflection films that are components of liquid crystal displays, a surface protection film is attached to temporarily protect the surface of the optical member. Such a surface protection film is used only in the manufacturing process of the optical member, and is peeled off and removed from the optical member when the optical member is assembled into a liquid crystal display. Since such a surface protection film for protecting the surface of the optical member is used only in the manufacturing process, it is also generally called a process film.

[0003] As described above, the surface protection film used in the process of manufacturing optical components has an adhesive layer formed on one side of an optically transparent polyethylene terephthalate (PET) resin film, and a release film that has been treated with a release agent to protect the adhesive layer until it is attached to the optical component is attached on top of the adhesive layer. In addition, optical components such as polarizing plates, retardation plates, and anti-reflection films are subjected to product inspection involving optical evaluation of the display performance, hue, contrast, and inclusion of foreign matter of the liquid crystal display panel with a surface protection film attached, so the required performance of the surface protection film is that the adhesive layer is free of air bubbles and foreign matter. Moreover, in recent years, when peeling off a surface protection film from an optical component such as a polarizing plate, a retardation plate, or an anti-reflection film, there has been concern that peeling charge generated by static electricity generated when the adhesive layer is peeled off from the adherend may affect failure of the electrical control circuit of a liquid crystal display, and therefore there is a demand for adhesive layers with excellent antistatic performance. Furthermore, when a surface protective film is attached to an optical component such as a polarizing plate, a retardation plate, or an antireflection film, the surface protective film may be peeled off once and then reattached for various reasons, and in such cases, the surface protective film is required to be easy to peel off from the optical component to which it is attached (reworkability). In addition, at this time, it is required that the adhesive does not contaminate the adherend, that is, that no adhesive residue is left behind. Furthermore, when the surface protection film is finally peeled off from an optical component such as a polarizing plate, a retardation plate, an antireflection film, etc., it is required that the surface protection film can be peeled off quickly. In other words, it is required that the adhesive strength does not change much depending on the peeling speed so that the surface protection film can be peeled off quickly even when peeled off at a high speed.

[0004] Thus, in recent years, the performance requirements for the adhesive layer constituting the surface protection film have been (1) to achieve a balance of adhesive strength at low and high peel speeds, (2) to prevent the occurrence of adhesive residue, (3) to have excellent antistatic properties, and (4) to have rework properties, in order to make the surface protection film easier to use. However, while it was possible to satisfy each of the required performance items (1) to (4) for the adhesive layer constituting the surface protection film individually, it was an extremely difficult task to simultaneously satisfy all of the required performance items (1) to (4) for the adhesive layer of the surface protection film. In this specification, the term "low speed region" refers to a peel speed of approximately 0.3 m / min, and the term "high speed region" refers to a peel speed of approximately 30 m / min.

[0005] For example, the following proposals are known regarding (1) balancing the adhesive strength in the low-speed region and the high-speed region of peel speed, and (2) preventing the occurrence of adhesive residue.

[0006] In an acrylic adhesive layer, the main component of which is a copolymer of a (meth)acrylic acid alkyl ester having an alkyl group with 7 or less carbon atoms and a copolymerizable compound containing a carboxyl group, and this is crosslinked with a crosslinking agent, there is a problem that when adhered for a long period of time, the adhesive transfers to the adherend and the adhesive strength to the adherend increases significantly over time. To avoid this, a known adhesive layer is provided in which a copolymer of a (meth)acrylic acid alkyl ester having an alkyl group with 8 to 10 carbon atoms and a copolymerizable compound having an alcoholic hydroxyl group is used and crosslinked with a crosslinking agent (Patent Document 1). Also proposed is a copolymer similar to the above, which is mixed with a small amount of a copolymer of an alkyl (meth)acrylate ester and a copolymerizable compound containing a carboxyl group, and is crosslinked with a crosslinking agent to provide an adhesive layer. However, when used for surface protection of a plastic plate or the like that has a low surface tension and a smooth surface, there are problems such as peeling phenomena such as lifting due to heating during processing or storage, and poor removability when peeled at high speeds that are used in manual work.

[0007] In order to solve these problems, a pressure-sensitive adhesive composition has been proposed in which a copolymer of a monomer mixture obtained by adding a) 100 parts by weight of a (meth)acrylic acid alkyl ester mainly composed of a (meth)acrylic acid alkyl ester having an alkyl group having 8 to 10 carbon atoms, b) 1 to 15 parts by weight of a carboxyl group-containing copolymerizable compound, and c) 3 to 100 parts by weight of a vinyl ester of an aliphatic carboxylic acid having 1 to 5 carbon atoms, is blended with a crosslinking agent in an amount equivalent to or greater than the carboxyl group of the above component b) (Patent Document 2). The adhesive composition described in Patent Document 2 is said to be free from peeling phenomena such as lifting during processing or storage, and has excellent removability without a significant increase in adhesive strength over time. It is also said to be able to be peeled off with a small force even after long-term storage, particularly long-term storage under a high-temperature atmosphere, without leaving any adhesive residue on the adherend, and able to be peeled off with a small force even when peeled off at high speed.

[0008] As for (3) excellent antistatic performance, a method of kneading an antistatic agent into a substrate film has been disclosed as a method for imparting antistatic properties to a surface protective film. Examples of the antistatic agent disclosed include (a) various cationic antistatic agents having cationic groups such as quaternary ammonium salts, pyridinium salts, and primary to tertiary amino groups, (b) anionic antistatic agents having anionic groups such as sulfonate groups, sulfate groups, phosphate groups, and phosphonate groups, (c) amphoteric antistatic agents such as amino acid-based and amino sulfate-based agents, (d) nonionic antistatic agents such as amino alcohol-based, glycerin-based, and polyethylene glycol-based agents, and (e) polymer-type antistatic agents obtained by increasing the molecular weight of the above-mentioned antistatic agents (Patent Document 3). In recent years, it has been proposed to incorporate such antistatic agents into the base film, or to incorporate the agent directly into the pressure-sensitive adhesive layer rather than coating the surface of the base film.

[0009] Regarding (4) rework performance, for example, a pressure-sensitive adhesive composition has been proposed in which an isocyanate compound curing agent and a specific silicate oligomer are blended in an acrylic resin in an amount of 0.0001 to 10 parts by weight per 100 parts by weight of the acrylic resin (Patent Document 4). In Patent Document 4, it is described that the main monomer component is an acrylic acid alkyl ester having an alkyl group with about 2 to 12 carbon atoms or a methacrylic acid alkyl ester having an alkyl group with about 4 to 12 carbon atoms, and that it may contain other functional group-containing monomer components such as a carboxyl group-containing monomer. In general, it is preferable to contain 50% by weight or more of the main monomer, and it is desirable that the content of the functional group-containing monomer component is 0.001 to 50% by weight, preferably 0.001 to 25% by weight, and more preferably 0.01 to 25% by weight. The pressure-sensitive adhesive composition described in Patent Document 4 is described as having reworkability because the change in cohesive strength and adhesive strength over time is small even at high temperature or high temperature and high humidity, and the adhesive strength to curved surfaces is also excellent. In general, when the adhesive layer is made soft, it is easy for adhesive residue to occur and reworkability to decrease. In other words, it is difficult to peel off when it is applied incorrectly, and it is difficult to reapply it. For this reason, it is considered necessary to crosslink a monomer having a functional group such as a carboxyl group to the base resin to give the adhesive layer a certain hardness in order to provide reworkability. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Japanese Patent Application Publication No. 63-225677 [Patent Document 2] Japanese Patent Application Publication No. 11-256111 [Patent Document 3] Japanese Patent Application Publication No. 11-070629 [Patent Document 4] Japanese Patent Application Publication No. 8-199130 Summary of the Invention [Problem to be solved by the invention]

[0011] In the prior art, the required performance of the pressure-sensitive adhesive layer constituting the surface protection film is as follows: (1) Achieving a balance in adhesive strength in the low-speed and high-speed peeling speed ranges, (2) preventing the occurrence of adhesive residue, (3) having excellent antistatic properties, and (4) having rework properties have been required. However, while it has been possible to satisfy each of the required properties (1) to (4) individually, it has not been possible to satisfy all the required properties required for the adhesive layer of a surface protection film.

[0012] The present invention has been made in consideration of the above circumstances, and has an object to provide an adhesive composition, an adhesive film, and a surface protection film that have excellent antistatic performance, an excellent balance of adhesive strength at low and high peel speeds, and further have excellent durability performance and rework performance. [Means for solving the problem]

[0013] In order to solve the above problems, the present invention provides a pressure-sensitive adhesive composition containing an acrylic polymer, an antistatic agent, and a crosslinking agent, wherein the acrylic polymer is a copolymer obtained by copolymerizing (A) at least one alkyl(meth)acrylate having an alkyl group having 4 to 10 carbon atoms, (B) at least one hydroxyl group-containing copolymerizable monomer, (C) at least one carboxyl group-containing copolymerizable monomer, and (G) at least one polyether compound having a polymerizable functional group, wherein the (B) hydroxyl group-containing copolymerizable monomer is at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide, and the (G) polyether compound having a polymerizable functional group is at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide. the ether compound is at least one selected from the group consisting of polyalkylene glycol mono(meth)acrylates, polyalkylene glycol di(meth)acrylates, alkoxypolyalkylene glycol (meth)acrylates, polyalkylene glycol monoallyl ethers, polyalkylene glycol diallyl ethers, alkoxypolyalkylene glycol allyl ethers, polyalkylene glycol monovinyl ethers, polyalkylene glycol divinyl ethers, and alkoxypolyalkylene glycol vinyl ethers; the pressure-sensitive adhesive composition further contains (F) a polyether-modified siloxane compound having an HLB value of 7 to 15, and the weight-average molecular weight (Mw) of the (F) polyether-modified siloxane compound is 600 or more and 10,000 or less; the antistatic agent is an ionic compound that is solid at a temperature of 30°C and has a melting point of more than 30°C and 50°C or less; and the crosslinking agent is a tri- or higher functional isocyanate compound.

[0014] In addition, the (A) alkyl (meth)acrylate having an alkyl group having 4 to 10 carbon atoms is preferably at least one selected from the group consisting of butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, and decyl (meth)acrylate.

[0015] In addition, it is preferable that the hydroxyl group-containing copolymerizable monomer is at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide.

[0016] In addition, it is preferable that the (C) carboxyl group-containing copolymerizable monomer is at least one selected from the group consisting of (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxypolycaprolactone mono(meth)acrylate, and 2-(meth)acryloyloxyethyl tetrahydrophthalic acid.

[0017] The crosslinking agent is preferably a tri- or higher functional isocyanate compound.

[0018] The present invention also provides a pressure-sensitive adhesive film comprising a resin film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition on one or both sides of the resin film.

[0019] The present invention also provides a surface protection film comprising a resin film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition on one side of the resin film. Effect of the Invention

[0020] According to the present invention, it is possible to satisfy all of the performance requirements for an adhesive layer of a surface protection film, which could not be achieved with conventional technology, and further, it is possible to obtain excellent antistatic performance and prevent the occurrence of adhesive residue. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will be described below based on preferred embodiments. The pressure-sensitive adhesive composition of the present invention is an antistatic agent-containing pressure-sensitive adhesive composition, which is composed of an acrylic polymer mainly composed of an alkyl (meth)acrylate having an alkyl group having 4 to 10 carbon atoms, and contains, relative to 100 parts by weight of the acrylic polymer, 85 to 98.5 parts by weight of the main component alkyl (meth)acrylate, 0.1 to 15 parts by weight of a hydroxyl group-containing copolymerizable monomer, 0.1 to 2 parts by weight of a carboxyl group-containing copolymerizable monomer, and 0.1 to 5 parts by weight of a crosslinking agent, wherein the acid value of the acrylic polymer is 0.01 to 8.0, and the antistatic agent is an ionic compound having a melting point of 30 to 50°C and contains a polyether-modified siloxane compound having an HLB value of 7 to 15.

[0022] The alkyl (meth)acrylate as the main component is preferably an alkyl (meth)acrylate having an alkyl group having 4 to 10 carbon atoms, and is preferably at least one selected from the group consisting of butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, and decyl (meth)acrylate. It is preferable that the main component, alkyl (meth)acrylate, is contained in an amount of 85 to 98.5 parts by weight per 100 parts by weight of the acrylic polymer.

[0023] Examples of the hydroxyl group-containing copolymerizable monomer include hydroxyalkyl (meth)acrylates and hydroxyl group-containing (meth)acrylamides. It is preferable that the compound is at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide. It is preferable that the composition contains 0.1 to 15 parts by weight of a hydroxyl group-containing copolymerizable monomer based on 100 parts by weight of the acrylic polymer.

[0024] The carboxyl group-containing copolymerizable monomer is preferably at least one selected from the group consisting of (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxypolycaprolactone mono(meth)acrylate, and 2-(meth)acryloyloxyethyl tetrahydrophthalic acid. It is preferable that the composition contains 0.1 to 2 parts by weight of a carboxyl group-containing copolymerizable monomer based on 100 parts by weight of the acrylic polymer.

[0025] In the pressure-sensitive adhesive composition of the present invention, it is preferable to crosslink the pressure-sensitive adhesive polymer when forming the pressure-sensitive adhesive layer. As a method for causing the crosslinking reaction, crosslinking may be performed by photocrosslinking using ultraviolet light (UV) or the like, but it is preferable that the pressure-sensitive adhesive composition contains a crosslinking agent. Examples of the crosslinking agent include bifunctional or trifunctional or higher isocyanate compounds, bifunctional or trifunctional or higher epoxy compounds, bifunctional or trifunctional or higher acrylate compounds, metal chelate compounds, etc. Among these, polyisocyanate compounds (bifunctional or trifunctional or higher isocyanate compounds) are preferred, and trifunctional or higher isocyanate compounds are more preferred. It is preferable that the crosslinking agent is contained in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of the acrylic polymer.

[0026] The trifunctional or higher isocyanate compound may be a polyisocyanate compound having at least three isocyanate (NCO) groups in one molecule. Polyisocyanate compounds are classified into aliphatic isocyanates, aromatic isocyanates, acyclic isocyanates, alicyclic isocyanates, and the like, and any of them may be used. Specific examples of polyisocyanate compounds include aliphatic isocyanate compounds such as hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), and trimethylhexamethylene diisocyanate (TMDI), and aromatic isocyanate compounds such as diphenylmethane diisocyanate (MDI), xylylene diisocyanate (XDI), hydrogenated xylylene diisocyanate (H6XDI), dimethyldiphenylene diisocyanate (TOID), and tolylene diisocyanate (TDI). Examples of trifunctional or higher isocyanate compounds include biuret modified diisocyanates (compounds having two NCO groups in one molecule) and isocyanurate modified diisocyanates, and adducts (polyol modified diisocyanates) with trivalent or higher polyols (compounds having at least three OH groups in one molecule) such as trimethylolpropane (TMP) and glycerin.

[0027] The pressure-sensitive adhesive composition of the present invention preferably contains an antistatic agent to impart antistatic properties. The antistatic agent is preferably a solid at room temperature (e.g., 30° C.), and more specifically, the antistatic agent is an ionic compound having a melting point of 30 to 50° C. The antistatic agent may be an ionic compound of quaternary ammonium salt type containing an acryloyl group. These antistatic agents are presumed to have a high affinity with acrylic polymers because they have a low melting point and contain long-chain alkyl groups.

[0028] The antistatic agent, which is an ionic compound having a melting point of 30 to 50°C, is an ionic compound having a cation and an anion, in which the cation is a nitrogen-containing onium cation such as a pyridinium cation, an imidazolium cation, a pyrimidinium cation, a pyrazolium cation, a pyrrolidinium cation, or an ammonium cation, or a phosphonium cation, a sulfonium cation, or the like, and the anion is a hexafluorophosphate (PF6 - ), thiocyanate (SCN - ), alkylbenzene sulfonate (RC6H4SO3 - ), perchlorate (ClO4 - ), tetrafluoroborate (BF4 - ) and other inorganic or organic anion compounds. By selecting the chain length of the alkyl group, the position and number of the substituent, and the like, it is possible to obtain one having a melting point of 30 to 50°C. The cation is preferably a quaternary nitrogen-containing onium cation, and examples thereof include quaternary pyridinium cations such as 1-alkylpyridinium (wherein the carbon atoms at positions 2 to 6 may be substituted or unsubstituted), quaternary imidazolium cations such as 1,3-dialkylimidazolium (wherein the carbon atoms at positions 2, 4, and 5 may be substituted or unsubstituted), and quaternary ammonium cations such as tetraalkylammonium. The antistatic agent, which is an ionic compound having a melting point of 30 to 50° C., is preferably contained in an amount of 0.1 to 5.0 parts by weight based on 100 parts by weight of the acrylic polymer.

[0029] The acryloyl group-containing quaternary ammonium salt type ionic compound is an ionic compound having a cation and an anion, the cation being (meth)acryloyloxyalkyltrialkylammonium [R + -C n H 2n -OCOCQ=CH2, where Q=H or CH3, R=alkyl], and the anion is hexafluorophosphate (PF6 - ), thiocyanate (SCN - ), organic sulfonates (RSO3 - ), perchlorate (ClO4- ), tetrafluoroborate (BF4 - ), F-containing imide salt (R F 2N - ) and other inorganic or organic anions. F 2N - )R F Examples of the F-containing imide salt include perfluoroalkanesulfonyl groups such as trifluoromethanesulfonyl and pentafluoroethanesulfonyl groups, and fluorosulfonyl groups. Examples of the F-containing imide salt include bis(fluorosulfonyl)imide salts [(FSO2)2N - 〕, bis(trifluoromethanesulfonyl)imide salt [(CF3SO2)2N - 〕, bis(pentafluoroethanesulfonyl)imide salt [(C2F5SO2)2N - and the like. The acryloyl group-containing quaternary ammonium salt type ionic compound is preferably copolymerized in the acrylic polymer in an amount of 0.1 to 5.0% by weight.

[0030] Specific examples of the antistatic agent are not particularly limited, but specific examples of the ionic compound having a melting point of 30 to 50° C. include 1-octylpyridinium dodecylbenzenesulfonate, 1-dodecylpyridinium thiocyanate, 3-methyl-1-dodecylpyridinium hexafluorophosphate, 1-dodecylpyridinium dodecylbenzenesulfonate, and 4-methyl-1-octylpyridinium hexafluorophosphate. Specific examples of the acryloyl group-containing quaternary ammonium salt type ionic compound include dimethylaminomethyl (meth)acrylate, hexafluorophosphate methyl salt [(CH3)3N + CH2OCOCQ=CH2 PF6 - , where Q=H or CH3], dimethylaminoethyl (meth)acrylate bis(trifluoromethanesulfonyl)imide methyl salt [(CH3)3N + (CH2)2OCOCQ=CH2·(CF3SO2)2N -, where Q=H or CH3], dimethylaminomethyl (meth)acrylate bis(fluorosulfonyl)imide methyl salt [(CH3)3N + CH2OCOCQ=CH2·(FSO2)2N - , where Q=H or CH3).

[0031] The pressure-sensitive adhesive composition of the present invention contains a polyether-modified siloxane compound having an HLB value of 7 to 15. The polyether-modified siloxane compound is a siloxane compound having a polyether group, and has a general siloxane unit [-SiR 1 2-O-], as well as siloxane units with polyether groups [-SiR 1 (R 2 O(R 3 O) n R 4 )-O-], where R 1 is one or more alkyl or aryl groups, R 2 and R 3 is one or more alkylene groups, R 4 indicates one or more alkyl or acyl groups (terminal groups). The polyether group is a polyoxyethylene group [(C2H4O) n 〕 and polyoxypropylene group〔(C3H6O) n ] and the like polyoxyalkylene groups. The molecular weight of the polyether-modified siloxane compound, in terms of weight average molecular weight (Mw), is preferably not more than 10000. From the viewpoint of compatibility with acrylic adhesives, the lower the HLB and the lower the molecular weight, the better the compatibility, but if the polyether-modified siloxane compound has a low molecular weight, excellent antistatic properties can be obtained even if the HLB is relatively high (compatibility with adhesives is somewhat low). It is also preferable that the polyether-modified siloxane compound is contained in an amount of 0.01 to 0.5 parts by weight based on 100 parts by weight of the acrylic polymer. HLB is the hydrophilic-lipophilic balance (hydrophilic-lipophilic ratio) defined in, for example, JIS K3211 (terminology for surfactants). Polyether-modified siloxane compounds can be obtained, for example, by grafting an organic compound having an unsaturated bond and a polyoxyalkylene group onto a polyorganosiloxane main chain having a silicon hydride group by a hydrosilylation reaction.Specific examples include dimethylsiloxane-methyl(polyoxyethylene)siloxane copolymer, dimethylsiloxane-methyl(polyoxyethylene)siloxane-methyl(polyoxypropylene)siloxane copolymer, and dimethylsiloxane-methyl(polyoxypropylene)siloxane polymer. By blending the polyether-modified siloxane compound in a pressure-sensitive adhesive composition, the adhesive strength and rework performance of the pressure-sensitive adhesive can be improved.

[0032] The pressure-sensitive adhesive composition of the present invention may contain a crosslinking retarder. Examples of the crosslinking retarder include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate, and β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone. These are ketoenol tautomer compounds, and in a pressure-sensitive adhesive composition using a polyisocyanate compound as a crosslinking agent, they can block the isocyanate group of the crosslinking agent, thereby suppressing excessive viscosity increase and gelation of the pressure-sensitive adhesive composition after the crosslinking agent is added, and can extend the pot life of the pressure-sensitive adhesive composition. The crosslinking retarder is preferably a keto-enol tautomeric compound, and more preferably at least one selected from the group consisting of acetylacetone and ethyl acetoacetate. When the crosslinking retarder is added, it is preferably contained in an amount of 1.0 to 5.0 parts by weight based on 100 parts by weight of the acrylic polymer.

[0033] The pressure-sensitive adhesive composition of the present invention may contain a crosslinking catalyst. The crosslinking catalyst may be any substance that functions as a catalyst for the reaction (crosslinking reaction) between the acrylic polymer and the crosslinking agent when a polyisocyanate compound is used as the crosslinking agent, and examples of the crosslinking catalyst include amine compounds such as tertiary amines, organotin compounds, organolead compounds, and organozinc compounds. Examples of tertiary amines include trialkylamines, N,N,N',N'-tetraalkyldiamines, N,N-dialkylaminoalcohols, triethylenediamine, morpholine derivatives, and piperazine derivatives. Examples of the organotin compound include dialkyltin oxide, fatty acid salts of dialkyltin, and fatty acid salts of stannous tin. The crosslinking catalyst is preferably an organotin compound, and more preferably at least one selected from the group consisting of dioctyltin oxide and dioctyltin dilaurate. When the crosslinking catalyst is added, it is preferable that the crosslinking catalyst is contained in an amount of 0.01 to 0.5 parts by weight relative to 100 parts by weight of the acrylic polymer.

[0034] The pressure-sensitive adhesive composition of the present invention may contain a polyether compound. The polyether compound is a compound having a polyalkylene oxide group, and examples thereof include polyether polyols such as polyalkylene glycols and derivatives thereof. Examples of the alkylene group of the polyalkylene glycol and the polyalkylene oxide group include, but are not limited to, an ethylene group, a propylene group, and a butylene group. The polyalkylene glycol may be a copolymer of two or more polyalkylene glycols such as polyethylene glycol, polypropylene glycol, and polybutylene glycol. Examples of the copolymer of polyalkylene glycol include polyethylene glycol-polypropylene glycol, polyethylene glycol-polybutylene glycol, polypropylene glycol-polybutylene glycol, and polyethylene glycol-polypropylene glycol-polybutylene glycol, and the copolymer may be a block copolymer or a random copolymer. Examples of the polyalkylene glycol derivatives include polyoxyalkylene alkyl ethers such as polyoxyalkylene monoalkyl ethers and polyoxyalkylene dialkyl ethers, polyoxyalkylene alkenyl ethers such as polyoxyalkylene monoalkenyl ethers and polyoxyalkylene dialkenyl ethers, polyoxyalkylene aryl ethers such as polyoxyalkylene monoaryl ethers and polyoxyalkylene diaryl ethers, polyoxyalkylene alkylphenyl ethers, polyoxyalkylene glycol fatty acid esters such as polyoxyalkylene glycol monofatty acid esters and polyoxyalkylene glycol difatty acid esters, polyoxyalkylene sorbitan fatty acid esters, polyoxyalkylene alkylamines, and polyoxyalkylene diamines. Here, examples of the alkyl ether in the polyalkylene glycol derivative include lower alkyl ethers such as methyl ether and ethyl ether, and higher alkyl ethers such as lauryl ether and stearyl ether. Examples of the alkenyl ether in the polyalkylene glycol derivative include vinyl ether, allyl ether, oleyl ether, etc. Examples of the fatty acid ester in the polyalkylene glycol derivative include saturated fatty acid esters such as acetates and stearic acid esters, and unsaturated fatty acid esters such as (meth)acrylic acid esters and oleic acid esters. The polyether compound is preferably a compound containing an ethylene oxide group, and more preferably a compound containing a polyethylene oxide group.

[0035] When the polyether compound has a polymerizable functional group, it can also be copolymerized with a (meth)acrylic polymer. As the polymerizable functional group, a vinyl functional group such as a (meth)acrylic group, a vinyl group, or an allyl group is preferable. As the polyether compound having a polymerizable functional group, polyalkylene glycol mono(meth)acrylic acid ester, polyalkylene glycol di(meth)acrylic acid ester, alkoxy polyalkylene glycol (meth)acrylic acid ester, polyalkylene glycol monoallyl ether, polyalkylene glycol diallyl ether, alkoxy polyalkylene glycol allyl ether, polyalkylene glycol monovinyl ether, polyalkylene glycol divinyl ether, alkoxy polyalkylene glycol vinyl ether, etc. can be mentioned.

[0036] Furthermore, as other components, known additives such as copolymerizable (meth)acrylic monomers containing alkylene oxides, (meth)acrylamide monomers, dialkyl-substituted acrylamide monomers, surfactants, curing accelerators, plasticizers, fillers, curing retarders, processing aids, antioxidants, antioxidants, etc. can be appropriately blended. These can be used alone or in combination of two or more kinds.

[0037] The acrylic polymer as the main component used in the pressure-sensitive adhesive composition of the present invention can be synthesized by copolymerizing an alkyl(meth)acrylate having an alkyl group with a carbon number of 4 to 10, a hydroxyl group-containing copolymerizable monomer, and a carboxyl group-containing copolymerizable monomer. The polymerization method for the acrylic polymer is not particularly limited, and any appropriate polymerization method such as solution polymerization or emulsion polymerization can be used. The acrylic polymer may be copolymerized with other monomers such as polyalkylene glycol mono(meth)acrylate monomers, nitrogen-containing vinyl monomers not containing a hydroxyl group, alkoxy group-containing alkyl(meth)acrylate monomers, and acryloyl group-containing quaternary ammonium salt-type ionic compounds. The pressure-sensitive adhesive composition of the present invention can be prepared by blending the above-mentioned acrylic polymer with a crosslinking agent, an antistatic agent, and further any additives as appropriate.

[0038] The acid value of the acrylic polymer is preferably 0.01 to 8.0, which can improve staining properties and improve the ability to prevent adhesive residue. Here, the "acid value" is an index representing the acid content, and is expressed as the number of milligrams of potassium hydroxide required to neutralize 1 g of a polymer containing a carboxyl group.

[0039] The adhesive layer obtained by crosslinking the adhesive composition preferably has an adhesive strength of 0.05 to 0.1 N / 25 mm at a peel speed of 0.3 m / min in the low-speed region, and an adhesive strength of 1.0 N / 25 mm or less at a peel speed of 30 m / min in the high-speed region. This provides performance in which the adhesive strength changes little depending on the peel speed, and enables rapid peeling even at high-speed peeling. In addition, even when the surface protection film is peeled off once for re-adhesion, excessive force is not required, and it is easy to peel off from the adherend.

[0040] The pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition has a surface resistivity of 5.0×10 +11 It is preferable that the surface resistivity is Ω / □ or less, and the peeling electrification voltage is ±0 to 0.5 kV. In the present invention, "±0 to 0.5 kV" means 0 to -0.5 kV and 0 to +0.5 kV, i.e., -0.5 to +0.5 kV. If the surface resistivity is high, the performance of dissipating static electricity generated by charging during peeling is poor. Therefore, by making the surface resistivity sufficiently small, the peeling electrification voltage caused by static electricity generated when the pressure-sensitive adhesive layer is peeled off from the adherend is reduced, and it is possible to suppress the influence on the electric control circuit of the adherend.

[0041] The gel fraction of the pressure-sensitive adhesive layer (crosslinked pressure-sensitive adhesive) obtained by crosslinking the pressure-sensitive adhesive composition of the present invention is preferably 95 to 100%. With such a high gel fraction, the adhesive strength is not excessively high at low peel speeds, and the elution of unpolymerized monomers or oligomers from the acrylic polymer is reduced, improving reworkability and durability at high temperatures and high humidity, and preventing contamination of the adherend.

[0042] The adhesive film of the present invention is formed by forming an adhesive layer formed by crosslinking the adhesive composition of the present invention on one side or both sides of a resin film. The surface protective film of the present invention is a surface protective film formed by forming an adhesive layer formed by crosslinking the adhesive composition of the present invention on one side of a resin film. The adhesive composition of the present invention has a well-balanced blend of each component, and therefore has excellent antistatic performance, an excellent balance of adhesive strength at low and high peel speeds, and also excellent durability and rework performance (no contamination transfer to the adherend after tracing the surface protective film with a ballpoint pen through the adhesive layer). Therefore, it can be suitably used as a surface protective film for polarizing plates, retardation plates, and antireflection films.

[0043] As the base film of the pressure-sensitive adhesive layer and the release film (separator) that protects the adhesive surface, a resin film such as a polyester film can be used. The substrate film may be subjected to an antifouling treatment using a silicone-based or fluorine-based release agent or coating agent, or silica microparticles or the like, or an antistatic treatment by coating or kneading an antistatic agent, on the side opposite to the side on which the pressure-sensitive adhesive layer of the resin film is formed. The release film is subjected to a release treatment with a silicone-based or fluorine-based release agent on the surface thereof that is to be joined to the adhesive surface of the adhesive layer. EXAMPLES

[0044] The present invention will now be described in detail with reference to examples.

[0045] <Production of acrylic polymer> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 90 parts by weight of 2-ethylhexyl acrylate, 8.5 parts by weight of 8-hydroxyoctyl acrylate, 1.0 part by weight of acrylic acid, and 60 parts by weight of a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65°C for 6 hours to obtain an acrylic polymer solution 1 used in Example 1 having a weight average molecular weight of 500,000. A part of the acrylic polymer was collected and used as a sample for measuring the acid value described later. [Examples 2 to 6 and Comparative Examples 1 to 3] The acrylic polymer solutions used in Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as in the acrylic polymer solution 1 used in Example 1 above, except that the monomer compositions were as shown in Table 1 (A) to (C), respectively. In Tables 1 and 2, (A) is the main component alkyl (meth)acrylate, (B) is a hydroxyl group-containing copolymerizable monomer, and (C) is a carboxyl group-containing copolymerizable monomer.

[0046] [Table 1]

[0047] <Production of Pressure-Sensitive Adhesive Composition and Surface Protective Film> [Example 1] To the acrylic polymer solution 1 of Example 1 produced as described above, 2.0 parts by weight of 1-octylpyridinium dodecylbenzenesulfonate and 0.1 parts by weight of a polyether-modified siloxane compound with an HLB of 7 (weight average molecular weight Mw is 10,000) were added and stirred, and then 1.0 parts by weight of Coronate HX (an isocyanurate of a hexamethylene diisocyanate compound) was added and mixed with stirring to obtain an adhesive composition of Example 1. This adhesive composition was applied onto a release film made of a silicone resin-coated polyethylene terephthalate (PET) film, and then dried at 90° C. to remove the solvent, thereby obtaining an adhesive sheet with an adhesive layer thickness of 25 μm. Thereafter, an adhesive sheet was transferred to the side opposite the antistatic and antifouling treated side of a polyethylene terephthalate (PET) film having one side treated with antistatic and antifouling treatment, thereby obtaining a surface protection film of Example 1 having a laminate structure of "antistatic and antifouling treated PET film / adhesive layer / release film (silicone resin coated PET film)". [Examples 2 to 6 and Comparative Examples 1 to 3] Surface protection films of Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as the surface protection film of Example 1 above, except that the compositions of the additives were as shown in Table 2 (D) to (F), respectively. In Tables 1 and 2, (D) is a crosslinking agent, (E) is an antistatic agent, and (F) is a polyether-modified siloxane compound.

[0048] [Table 2]

[0049] In Table 1, the weight parts are shown in parentheses, with the total of groups (A) to (C) being 100 parts by weight, except that in Example 1, the total of groups (A) to (C) is 99.5 parts by weight, in Example 3 it is 98.5 parts by weight, and in Example 4 it is 101 parts by weight. The compound names of the abbreviations of each component used in Table 1 are shown in Table 2. Coronate (registered trademark) HX, Coronate (registered trademark) HL, and Coronate (registered trademark) L are product names of Nippon Polyurethane Industry Co., Ltd., and Takenate (registered trademark) D-140N, D-127N, and D-110N are product names of Mitsui Chemicals, Inc.

[0050] <Test methods and evaluation> The surface protection films in Examples 1 to 6 and Comparative Examples 1 to 3 were aged for 7 days under an atmosphere of 23°C and 50% RH, and then the release film (a silicone resin-coated PET film) was peeled off to expose the adhesive layer, which was used as a sample for measuring surface resistivity. Furthermore, this surface protection film with the adhesive layer exposed was attached to the surface of a polarizing plate attached to a liquid crystal cell via the adhesive layer, and after leaving it for one day, it was autoclaved at 50°C and 5 atmospheres for 20 minutes and then left at room temperature for a further 12 hours to prepare a sample for measuring adhesive strength, peeling charge voltage, reworkability, and durability.

[0051] <Acid value> The acid value of the acrylic polymer was measured by dissolving the sample in a solvent (a mixture of diethyl ether and ethanol in a volume ratio of 2:1) and titrating it with an automatic potentiometric titrator (Kyoto Electronics Manufacturing Co., Ltd., AT-610) using a 0.1 mol / l potassium hydroxide ethanol solution. The amount of potassium hydroxide ethanol solution required to neutralize the sample was measured. The acid value was then calculated using the following formula. Acid value = (B × f × 5.611) / S B = Amount (ml) of 0.1 mol / l potassium hydroxide ethanol solution used in titration f=factor of 0.1 mol / l potassium hydroxide ethanol solution S = mass of solids in the sample (g)

[0052] <Adhesive strength> The measurement sample obtained above (a 25 mm wide surface protection film bonded to the surface of a polarizing plate) was peeled in a 180° direction using a tensile tester at a peel speed in the low speed range (0.3 m / min) and a peel speed in the high speed range (30 m / min), and the peel strength measured was taken as the adhesive strength.

[0053] <Surface resistivity> After aging and before bonding to a polarizing plate, the release film (a silicone resin-coated PET film) was peeled off to expose the adhesive layer, and the surface resistivity of the adhesive layer was measured using a resistivity meter, Hiresta UP-HT450 (manufactured by Mitsubishi Chemical Analytech).

[0054] <Peeling charge voltage> The measurement sample obtained above was peeled off at an angle of 180° at a tensile speed of 30 m / min, and the voltage (charged voltage) generated by the charging of the polarizing plate was measured using high-precision electrostatic sensors SK-035 and SK-200 (manufactured by Keyence Corporation). The maximum measured value was taken as the peeling charged voltage.

[0055] <Reworkability> The surface protection film of the measurement sample obtained above was traced with a ballpoint pen (load 500 g, 3 round trips), and then the surface protection film was peeled off from the polarizing plate and the surface of the polarizing plate was observed to confirm that there was no contamination transfer to the polarizing plate. The evaluation target criteria were as follows: "○" if there was no contamination transfer to the polarizing plate, "△" if contamination transfer was confirmed in at least a part along the track traced with the ballpoint pen, and "×" if contamination transfer was confirmed along the track traced with the ballpoint pen and adhesive detachment was confirmed from the adhesive surface.

[0056] <Durability> The measurement samples obtained above were left in an atmosphere of 60°C and 90% RH for 250 hours, then removed to room temperature and left for another 12 hours, after which the adhesive strength was measured and it was confirmed that there was no clear increase compared to the initial adhesive strength. The evaluation target criteria were as follows: if the adhesive strength after the test was 1.5 times or less of the initial adhesive strength, it was evaluated as "○", and if it exceeded 1.5 times, it was evaluated as "×".

[0057] The evaluation results are shown in Table 3. The surface resistivity is expressed as "m×10 +n " is expressed as "mE+n" (where m is any real value and n is a positive integer).

[0058] [Table 3]

[0059] The surface protection films of Examples 1 to 6 had an adhesive strength of 0.05 to 0.1 N / 25 mm at a peel speed of 0.3 m / min in the low-speed region, an adhesive strength of 1.0 N / 25 mm or less at a peel speed of 30 m / min in the high-speed region, and a surface resistivity of 5.0 × 10 +11 The peeling charge voltage was less than Ω / □, the peeling charge voltage was ±0 to 0.5 kV, and after tracing the surface protection film with a ballpoint pen through the adhesive layer, no contamination was transferred to the adherend, and the film also had excellent durability when left in an atmosphere of 60°C and 90% RH for 250 hours. In other words, it simultaneously meets all the required performance requirements: (1) balancing adhesive strength at low and high peel speeds, (2) preventing the occurrence of adhesive residue, (3) having excellent antistatic properties, and (4) having reworkability.

[0060] The surface protection film of Comparative Example 1 had a small amount of the main component alkyl (meth)acrylate, an excessive amount of a hydroxyl group-containing copolymerizable monomer, no carboxyl group-containing copolymerizable monomer, and an excessively large HLB value of the polyether-modified siloxane compound, and therefore had low adhesive strength at a peel speed of 0.3 m / min in the low-speed region, high surface resistivity and peel charging voltage, and poor durability. The surface protection film of Comparative Example 2 contained an excess of carboxyl group-containing copolymerizable monomer relative to the main component alkyl (meth)acrylate, which resulted in an excessively short pot life and crosslinking that had progressed before coating, making it impossible to coat. The surface protection film of Comparative Example 3 did not contain a carboxyl group-containing copolymerizable monomer, and the Mw of the polyether-modified siloxane compound was excessively large, so that the surface resistivity and peeling electrification voltage were high and the reworkability was somewhat poor. Thus, the surface protection films of Comparative Examples 1 to 3 were unable to simultaneously satisfy all of the required performance requirements: (1) balancing adhesive strength at low and high peel speeds, (2) preventing the occurrence of adhesive residue, (3) having excellent antistatic performance, and (4) having rework performance.

Claims

[Claim 1] The polymer is made of an acrylic polymer mainly composed of an alkyl (meth)acrylate having an alkyl group having 4 to 10 carbon atoms, the composition contains, relative to 100 parts by weight of the acrylic polymer, 85 to 98.5 parts by weight of the alkyl (meth)acrylate as the main component, (500 / 101) to 15 parts by weight of a hydroxyl group-containing copolymerizable monomer, 0.1 to (100 / 99.5) parts by weight of a carboxyl group-containing copolymerizable monomer, and 0.1 to 5 parts by weight of a crosslinking agent; the acid value of the acrylic polymer is 0.01 to 8.0; The antistatic agent is a pressure-sensitive adhesive layer formed by crosslinking a pressure-sensitive adhesive composition containing an ionic compound having a melting point of 30 to 50° C. on one or both sides of a resin film; An adhesive film characterized in that the adhesive strength is 0.05 to 0.1 N / 25 mm at a peel speed of 0.3 m / min, and is 1.0 N / 25 mm or less at a peel speed of 30 m / min.

Citation Information

Patent Citations

  • Acrylic adhesive composition

    JP1997302321A

  • Pressure-sensitive adhesive composition and surface protection film

    JP2012224811A

  • Pressure-sensitive adhesive composition and surface protection film

    JP2013107977A

  • Tacky adhesive composition, and optical member surface protecting film

    JP2013163744A

  • Adhesive composition, adhesive film, and surface protective film

    JP2015021114A